2020
DOI: 10.3126/jmcjms.v8i2.33972
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antimicrobial Susceptibility Pattern of Pseudomonas aeruginosa Isolated from Various Clinical Samples in a Tertiary Care Hospital

Abstract: Background and Objectives: Pseudomonas aeruginosa is one of the leading causes of hospital acquired infections. Increased resistance in this organism continues to pose a significant threat to patient care because of limited therapeutic options. The main objective of this study was to find out the prevalence and current antimicrobial susceptibility pattern of P. aeruginosa isolates obtained from various clinical samples at a tertiary care hospital. Material and Methods: The study was conducted in a tertia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…In our study, half of the total isolates were found to be multidrug resistant. Such high rates of MDR P. aeruginosa were also reported in previous studies from Nepal that ranges from 50 to 55.5% [ 25 , 27 ].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In our study, half of the total isolates were found to be multidrug resistant. Such high rates of MDR P. aeruginosa were also reported in previous studies from Nepal that ranges from 50 to 55.5% [ 25 , 27 ].…”
Section: Discussionsupporting
confidence: 77%
“…Therefore, our findings infers that P. aeruginosa is one of the predominant organism to cause respiratory tract infections. P. aeruginosa are developing resistance to different anti-pseudomonal drugs via various mechanisms that is resulting them to develop into most dangerous and dreaded bug [ 22 , 27 ]. In our study, half of the total isolates were found to be multidrug resistant.…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies reported a higher resistance figure with ceftazidime, contrary to ours. A study by Maharjan 51 reported about 53% resistance with ceftazidime, and similar figures (49%) were also reported by Mahaseth et al, 69 whereas Shidiki et al, 71 (90%) reported a comparatively very higher figure of resistance with ceftazidime. However, current analysis, isolates of P. aeruginosa were moderately susceptible to imipenem, ciprofloxacin, levofloxacin, and gentamycin.…”
Section: Discussionsupporting
confidence: 62%
“….Adedeji et al, in their study conducted in Africa on various clinical samples, observed a higher prevalence (50%) of P. aeruginosa in ear infections68 . A study conducted by Mahaseth et al, reported a prevalence of 11.6% in the clinical samples69 . The study by Maharjan et al, conducted on 1049 clinical samples showing growth reported a lower prevalence of P. aeruginosa in the clinical samples51 .…”
mentioning
confidence: 96%
“…The prominence of multidrug resistant P. aeruginosa is growing in the world, limiting the therapeutic options (26,27). Despite the emergence of modern antibacterial agents with anti-Pseudomonal activity, P. aeruginosa continues to be the leading cause of lifethreatening infections in hospitals (28,29). Even though increase of multi-drug resistant Pseudomonas aeruginosa strains, which are intractable to be treated, some available antibiotics still able to dominate pseudomonal infections with a reasonable percentage of success, for example, colistin sulfate and quinolones (ciprofloxacin and levofloxacin) (30,31).…”
Section: Introductionmentioning
confidence: 99%